ANALISIS PENGARUH ALKALISASI NaOH TERHADAP SERAT NANAS SEBAGAI PENGUATAN BIO KOMPOSIT - widodo, edi; Dwiyoga, Ilham (Otopro, 2023)
This research focuses on the utilization of natural fibers as a reinforced composite material from pineapple leaf fiber with concentrations of Alkali NaOH 5%, 10%, 15% using a polyester resin matrix. In this study, the experimental design uses the printing method, which aims to design experiments to analyze experimental data, and is also used to determine the minimum number of experiments obtained and provide information on factors that affect parameters. The experiments were carried out through 1) Composite manufacturing method, 2) NaOH liquid preparation, 3) Tensile test method, 3) FTIR test method, 4) Fiber molding. The results of the research using FT-IR (Fourier Transform Infared Spectroscopy) test data can be evaluated into specific functional groups found in each branch of the Pineapple Leaf fiber, respectively, namely fiber with 5%, 10%, 15% NaOH treatment. The results showed that the specimen with 50% treatment, where the tensile strength value was 129 N/mm2 and the maximum load was 19.85 N, and the elongation in the area of the highest tensile test load was obtained in specimen 2, namely 10% treatment with a value of 3.29 mm so that there was the influence of the fiber strength value received on the treatment of NaOH compounds, if the NaOH compound is less then it has a little effect on the pineapple leaf fiber, while the more NaOH compound has the better received effect with a high percentage yield.